Fair trade in Brazil: current status, constraints and opportunities - Bossle, Marilia Bonzanini; Neutzling, Daiane Mulling; Wegner, Douglas; Bitencourt, Claudia Cristina (Organizações & Sociedade, 2017)
Fair trade has expanded worldwide but there is a lack of information regarding to this kind of organizations in emerging countries. This study aims to identify the characteristics, constraints and opportunities for fair trade organizations in Brazil. In order to achieve this goal we analyzed a database of 277 Brazilian organizations linked to fair trade networks, followed by an analysis of Brazilian experts’ opinions on fair trade market in Brazil. Results show that the number of fair trade organizations has highly increased between 2005 and 2012 due to the support of institutions and public agencies. Organizations still face difficulties to become economic viable and generate income to their members. Brazilian producers continue to need support and assistance to minimize legal and managerial challenges. Fair trade has a social role and a political nature, what might call attention of policy makers regarding social programs and the support of fair trade organizations.